2011
DOI: 10.1016/j.sbspro.2011.09.260
|View full text |Cite
|
Sign up to set email alerts
|

What is the Eye Doing during Reading Aloud? Eye-Voice Span in Acquired Dyslexia

Abstract: truefalse2016-03-16T23:02:09

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Since lexical route processes are less dependent from word length than the grapheme-to-phoneme conversion processes of the sublexical route (Weekes, 1997; Rastle and Coltheart, 1998, 1999; Ziegler et al, 2001; Juphard et al, 2004; Zoccolotti et al, 2005; Barton et al, 2014), we also test for frequency × length interactions on offset EVS and we expect that the offset EVS of low familiarity words show increased length effects than the offset EVS of low-familiarity ones. To our knowledge, word familiarity effects on EVS have only been investigated by Halm et al (2011), who found frequency effects on spatial EVS but not on temporal EVS. Since this paper is a very brief one, and the authors do not specify whether they measured the onset EVS or the offset EVS, uncertainty remains.…”
Section: Introductionmentioning
confidence: 97%
“…Since lexical route processes are less dependent from word length than the grapheme-to-phoneme conversion processes of the sublexical route (Weekes, 1997; Rastle and Coltheart, 1998, 1999; Ziegler et al, 2001; Juphard et al, 2004; Zoccolotti et al, 2005; Barton et al, 2014), we also test for frequency × length interactions on offset EVS and we expect that the offset EVS of low familiarity words show increased length effects than the offset EVS of low-familiarity ones. To our knowledge, word familiarity effects on EVS have only been investigated by Halm et al (2011), who found frequency effects on spatial EVS but not on temporal EVS. Since this paper is a very brief one, and the authors do not specify whether they measured the onset EVS or the offset EVS, uncertainty remains.…”
Section: Introductionmentioning
confidence: 97%
“…FA has good accuracy in comparison to manual segmentation (Hosom, 2009;Malfrère et al, 2003;Yuan & Liberman, 2008). Time indices in segmentation files can be aligned with time stamps in the eye-movement record to determine asynchronies between gaze targets and speech production, the eye-voice span (EVS; Halm et al, 2011;Inhoff et al, 2011;Morton, 1964). EVS provides another target for simulation work, beyond pure gaze measures.…”
Section: C22 Speech Analysis/segmentationmentioning
confidence: 99%